Iskanje dodatnih virov zaslužka na podeželju - Potočnik Slavič, Irma (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The issue on supplementary activities on farms as also their impact on farm income does not represent a new phenomena in Slovenia, but a new fluorishing wave is to be seen in the last decade in the area of diversification and extent. The article analyses the motives of accelerated development of supplementary activities, reveals the newest legislation and through the case study of farms in Ljubljana basin indicates the geographical aspect of supplementary activities on farms.
Keywords: agriculture; dohodek; dopolnilne dejavnosti; kmetijstvo; podeželje; rural area; Slovenia; Slovenija